1 if x 1692 f x 23 0 2 38 1 1 1 1 1 1 x 0

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: x2 2 -2 2 -2 2 -2 (d) f (1) = √ -6 √ 2 2 3 and f (1) = √ so the tangent line has the equation y − 3 = √ (x − 1). 3 3 3 0 2 0 54. (a) (c) 0.5 f (x) = 2x cos x2 cos x − sin x sin x2 1.2 ^ ^ 0 6 6 -1.2 87 Chapter 3 (d) f (1) = sin 1 cos 1 and f (1) = 2 cos2 1 − sin2 1, so the tangent line has the equation y − sin 1 cos 1 = (2 cos2 1 − sin2 1)(x − 1). 0.8 ^ 6 0 (a) dy/dt = −Aω sin ωt, d2 y/dt2 = −Aω 2 cos ωt = −ω 2 y (b) one complete oscillation occurs when ωt increases over an interval of length 2π , or if t increases over an interval of length 2π/ω (c) f = 1/T (d) 55. amplitude = 0.6 cm, T = 2π/15 s/oscillation, f = 15/(2π ) oscillations/s 56. dy/dt = 3A cos 3t, d2 y/dt2 = −9A sin 3t, so −9A sin 3t + 2A sin 3t = 4 sin 3t, −7A sin 3t = 4 sin 3t, −7A = 4, A = −4/7 57. (a) p ≈ 10 lb/in2 , dp/dh ≈ −2 lb/in2 /mi (b) dp dh dp = ≈ (−2)(0.3) = −0.6 lb/in2 /s dt dh dt 58. (a) (b) 59. 45 dF 45(− sin θ + 0.3 cos θ) , =− ; cos θ + 0.3 sin θ dθ (cos θ + 0.3 sin θ)2 if θ = 30◦ , then dF/dθ ≈ 10.5 lb/rad ≈ 0.18 lb/deg F= dF dθ dF = ≈ (0.18)(−0.5) = −0.09 lb/s dt dθ dt With u = sin x, d d du d d (| sin x|) = (|u|) = (|u|) = (|u|) cos x = dx dx du dx du cos x, sin x &gt; 0 = − cos x, sin x &lt; 0 = 60. (a) cos x, 0&lt;x&lt;π − cos x, −π &lt; x &lt; 0 d d (cos x) = [sin(π/2 − x)] = − cos(π/2 − x) = − sin x dx dx 61. cos x, − cos x, (b) (c) 62. (a) (b) for x = 0, f (x) = x cos lim x sin x→0 1 x − 1 x2 + sin 1 1 1 1 = − cos + sin x x x x 1 = 0 = f (0) x 1 h sin f (0 + h) − f (0) h = lim sin 1 , which does not exist = lim lim h→0 h→0 h→0 h h h f (x) = x2 cos lim x2 sin x→0 1 x − 1 = 0 = f (0) x 1 x2 + 2x sin 1 1 1 = − cos + 2x sin , x = 0 x x x u&gt;0 u&lt;0 Exercise Set 3.5 (c) (d) 88 1 h2 sin f (0 + h) − f (0) h = lim h sin 1 = 0 = lim f (0) = lim h→0 h→0 h→0 h h h 1 lim f (x) does not exist because cos oscillates between 1 and −1 x→0 x g (x) = 3[f (x)]2 f (x), g (2) = 3[f (2)]2 f (2) = 3(1)2 (7) = 21 h (x) = f (x3 )(3x2 ), h (2) = f (8)(12) = (−3)(12) = −36 (a) F (x) = f (g (x))g (x), F (−1) = f (g (−1))g (−1) = f (2)(−3) = (4)(−3) = −12 (b) 64. (a) (b) 63. G (x) = g (f (x))f (x), G (−1) = g (f (−1))f (−1) = g (2)(3) = (−5)(3) = −15 65. (f ◦ g ) (x) = f (g (x))g (x) so (f ◦ g ) (0) = f (g (0))g (0) = f (0)(3) = (2)(3) = 6 66. F (x) = f (g (x))g (x) = 67. √ √ 1 3x − 1 3 3 √ = = F (x) = f (g (x))g (x) = f ( 3x − 1) √ (3x − 1) + 1 2 3x − 1 2x 2 3x − 1 68. d [f (x2 )] = f (x2 )(2x), thus f (x2 )(2x) = x2 so f (x2 ) = x/2 if x = 0 dx 69. 70. √ 3(x2 − 1) + 4(2x) = 2x 3x2 + 1 d 2 d [f (3x)] = f (3x) (3x) = 3f (3x) = 6x, so f (3x) = 2x. Let u = 3x to get f (u) = u; dx dx 3 2 d [f (x)] = f (x) = x. dx 3 (a) If f (−x) = f (x), then d d [f (−x)] = [f (x)], f (−x)(−1) = f (x), f (−x) = −f (x) so dx dx f is odd. (b) d d [f (−x)] = − [f (x)], f (−x)(−1) = −f (x), f (−x) = f (x) so dx dx If f (−x) = −f (x), then f is even. 71. For an even function, the graph is symmetric about the y -axis; the slope of the tangent line at (a, f (a)) is the negative of the slope of the tangent line at (−a, f (−a). For an odd function, the graph is symmetric about the origin; the slope of the tangent line at (a, f (a)) is the same as the slope of the tangent line at (−a, f (−a). y y f(x) f(x) f '(x) x x f '(x) 72. dy du dv dw dy = dx du dv dw dx 73. d d [f (g (h(x)))] = [f (g (u))], dx dx = u = h(x) du du d [f (g (u))] = f (g (u))g (u) = f (g (h(x)))g (h(x))h (x) du dx dx 89 Chapter 3 EXERCISE SET 3.6 1. (a) dy = f (x)dx = 2xdx = 4(1) = 4 and ∆y = (x + ∆x)2 − x2 = (2 + 1)2 − 22 = 5 (b) y ∆y dy 4 2 2. (a) dy = 3x2 dx = 3(1)2 (1) = 3 and ∆y = (x + ∆x)3 − x3 = (1 + 1)3 − 13 = 7 (b) x 3 y 8 ∆y dy (1,1) 1 dx 1 3. (a) dy = (−1/x2 )dx = (−1)(−0.5) = 0.5 and ∆y = 1/(x + ∆x) − 1/x = 1/(1 − 0.5) − 1/1 = 2 − 1 = 1 x 2 y (b) 2 ∆y = 1 dy = 0.5 1 x 0.5 4. √ (a) dy = (1/2 x)dx = (1/(2 · 3))(−1) = −1/6 ≈√ 0.167 and − √ √ √ ∆y = x + ∆x − x = 9 + (−1) − 9 = 8 − 3 ≈ −0.172 1 y (b) 3 dy = – 0.167 ∆ y = – 0.171 x 8 5. dy = 3x2 dx; ∆y = (x + ∆x)3 − x3 = x3 + 3x2 ∆x + 3x(∆x)2 + (∆x)3 − x3 = 3x2 ∆x + 3x(∆x)2 + (∆x)3 6. dy = 8dx; ∆y = [8(x + ∆x) − 4] − [8x − 4] = 8∆x 7. dy = (2x − 2)dx; ∆y = [(x + ∆x)2 − 2(x + ∆x) + 1] − [x2 − 2x + 1] = x2 + 2x ∆x + (∆x)2 − 2x − 2∆x + 1 − x2 + 2x − 1 = 2x ∆x + (∆x)2 − 2∆x 8. dy = cos x dx; ∆y = sin(x + ∆x) − sin x 9 Exercise Set 3.6 9. (a) 90 dy = (12x2 − 14x)dx (b) dy = x d(cos x) + cos x dx = x(− sin x)dx + cos xdx = (−x sin x + cos x)dx 10. (a) dy = (−1/x2 )dx 11. (a) dy = (b) dy = −17(1 + x)−18 dx (a) dy = (x3 − 1)d(0) − (1)d(x3 − 1) (x3 − 1)(0) − (1)3x2 dx 3x2 = =− 3 dx (x3 − 1)2 (x3 − 1)2 (x − 1)2 (b) dy = (2 − x)(−3x2 )dx − (1 − x3 )(−1)dx 2x3 − 6x2 + 1 = dx (2 − x)2 (2 − x)2 (a) f (x) ≈ f (1) + f (1)(x − 1) = 1 + 3(x − 1) (c) From...
View Full Document

Ask a homework question - tutors are online